Research on the Inheritance Value and Communication Innovation of “Hua'er” Folk Songs in the Era of Digital Intangible Cultural Heritage (Mongolian Journal of Arts and Culture, 2025)
As a traditional folk song listed in the UNESCO Representative List of the Intangible Cultural Heritage of Humanity, “Hua’er” (花儿) carries the cultural genes and emotional memories of multiple ethnic groups in Northwest China. In the new stage of intangible cultural heritage protection where digital technology has fully penetrated, the inheritance mode and dissemination path of “Hua’er” (花儿) are undergoing profound changes. Supported by the theory of digital intangible cultural heritage, this paper combines typical cases such as the inheritance practice of “Hua’er” (花儿) in Min County, systematically analyzes the inheritance value of “Hua’er” (花儿) folk songs in the digital era in terms of cultural gene preservation, ethnic identity construction, and cultural tourism integration empowerment. It deeply explores the innovative dissemination paths in areas such as short video dissemination, crossborder art innovation, and digital cultural tourism integration. Furthermore, it proposes optimization strategies for practical dilemmas such as cultural distortion and technical adaptation, providing theoretical references and practical paradigms for the living inheritance of traditional folk song-type intangible cultural heritage.